UNDERSTANDING BEHAVIOR OF DIGITAL MONEY APPLICATION USAGE ON ADOLESCENTS - Pratika, Yeyen (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
Information technology has changed the existing transaction process from manual to digital-based. The presence of financial technology, especially digital money drives to the high competition. Companies apply various marketing strategies to win the market competition. The mechanism of cashback promotion is mostly provided by digital money companies as their marketing strategies to attract customers. Cashback promotion program triggers a change of customer behavior to use digital money due to cashback promotion. This study aims to examine the factors that influence the use of digital money application on adolescents by using hedonic and utilitarian motivation, behavior aspect, intention to use and usage behavior. This studies used path analysis by utilizing the SmartPLS program. This study involved 113 respondents who have digital money application on their smartphone. The result found that hedonic motivation, utilitarian motivation and behavior aspect have a positive effect on the intention of use. In addition, intention of use also has a positive influence on usage behavior.